KAPASITAS DAYA DUKUNG TIANG PANCANG JEMBATAN AIR MANGGALA PRABUMULIH DENGAN METODE MAYERHOF DAN METODE ENR - Dimitri Yulianti; Bahder Djohan (JURNAL ILMIAH BERING'S, 2021)
Pile foundation structures in a building are generally used if the subgrade under the building does not have sufficient bearing capacity to bear the weight of the building. The data needed to analyze the bearing capacity of these piles was from the measurement results in the field in the form of SPT and calendering data. In this paper, calculated the bearing capacity of the pile analytically from the results of calendering and standart penetration test (SPT), calculated using the Mayerhoff and ENR method. And the results of the SPT calculation showed that the net weight value or N (the amount of load received by each pile) imposed on the pile was 132.04 tons, from the calculation of the pile bearing capacity ≤ 200 tons and qualified for the safety requirements of the foundation to the soil bearing capacity. From the results of the ENR method, the largest pile bearing capacity was 305.16 tons with a value of S (the number of pile penetrations of 10 blows) was 0.002 m.